Combinations of Tense Forms in Serbian Folk Epic Poetry - Čarkić, Milosav Ž. (Stylistyka, 2021)
In this paper the author is dealing with combinations of tense forms in Serbian folk epic poetry and he statistically proves that the present tense is the predominant tense form in this kind of Serbian folk poetry. He is trying to discover the main reasons for such use of the present tense. As regards combinations of tense forms in Serbian folk epic poetry, they are rather free and depend, primarily, on the manner of presenting the epic content and on the length of the poem, but there is above all a certain regularity resulting in firm systems.